The Executive Checklist - Kerr, James (Ascent Audio, 2020)
A guide for new executives that explores how to create an overarching, enterprise-wide transformative program. The book provides a best-practice checklist for eight core areas: Strategy Setting, Technology Alignment, Business Renovation, Project Management, Communications Renewal, Employee Engagement, Staff Transformation, and Organizational Design.
Online resource; Title from title page (viewed May 19, 2020)
Keywords: Industrial management; Strategic planning; Organizational effectiveness; Organizational change; Organizational Innovation; Gestion d'entreprise; Planification stratégique; Efficacité organisationnelle; Changement organisationnel; Audiobooks